Genetic predisposition to metabolic dysfunction-associated fatty liver disease - O.E. Abaturov; A.O. Nikulina (Zaslavsky O.Yu., 2024)
The literature review highlights the issue of genetic risk factors associated with the development of metabolic dysfunction-associated fatty liver disease. Human genetic examinations revealed 132 genes among which 32 loci are strongly associated with the pathogenesis of metabolic dysfunction-associated fatty liver disease. It has been found that the risk of developing metabolic dysfunction-associated fatty liver disease is carried by single-nucleotide variants of various genes whose products are involved in lipid and carbohydrate metabolism, maintenance of the redox state, the development of inflammation and fibrosis of liver tissue, which are components of metabolic dysfunction-associated fatty liver disease reactome. The authors presented a detailed list of genetic factors singling out those that influence the risk of metabolic dysfunction-associated fatty liver disease and directly metabolic dysfunction-associated steatohepatitis and liver fibrosis. Also, they emphasized that it is the single-nucleotide variants of the genes of protein 3 containing a patatin-like phospholipase domain, transmembrane 6 superfamily member 2, and 17b-hydroxysteroid dehydrogenase type 13 that are characterized by the highest degree of association with metabolic dysfunction-associated fatty liver disease (odds ratio > 1.6) compared to single-nucleotide variants of other genes identified by gene association studies. The combination of several polymorphisms increases the risk of development and severity of metabolic dysfunction-associated fatty liver disease. The additive steatogenic effect of protein 3 single-nucleotide gene variants containing a patatin-like phospholipase domain and transmembrane 6 superfamily member 2 is probably due to an increased expression of genes involved in de novo lipogenesis. The authors emphasize the need for genetic risk assessment of metabolic dysfunction-associated fatty liver disease, which should include molecular genetic testing at an early stage of examination.